2001
DOI: 10.1103/physrevb.63.092401
|View full text |Cite
|
Sign up to set email alerts
|

Memory and superposition in a spin glass

Abstract: Non-equilibrium dynamics in a Ag(Mn) spin glass are investigated by measurements of the temperature dependence of the remanent magnetisation. Using specific cooling protocols before recording the thermo- or isothermal remanent magnetisations on re-heating, it is found that the measured curves effectively disclose non-equilibrium spin glass characteristics such as ageing and memory phenomena as well as an extended validity of the superposition principle for the relaxation. The usefulness of this "simple" dc-met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
150
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(168 citation statements)
references
References 11 publications
18
150
0
Order By: Relevance
“…These experiments showed not only rejuvenation effects but also that spin glass order, characteristic of different temperatures, can coexist on different length scales; hence the spin glass keeps a memory of its thermal history. A simple experimental protocol [85] was employed to illustrate memory and rejuvenation effects [110][111][112][113]; the sample is cooled from a high temperature with one (or more) halts of the cooling at one (or more) temperatures in the spin glass phase. The experimental procedure of a double-stop experiment is illustrated in Fig.…”
Section: Experiments: Aging Memory and Rejuvenationmentioning
confidence: 99%
“…These experiments showed not only rejuvenation effects but also that spin glass order, characteristic of different temperatures, can coexist on different length scales; hence the spin glass keeps a memory of its thermal history. A simple experimental protocol [85] was employed to illustrate memory and rejuvenation effects [110][111][112][113]; the sample is cooled from a high temperature with one (or more) halts of the cooling at one (or more) temperatures in the spin glass phase. The experimental procedure of a double-stop experiment is illustrated in Fig.…”
Section: Experiments: Aging Memory and Rejuvenationmentioning
confidence: 99%
“…[5][6][7][8][9] Very recently, Sun et al performed a series of measurements on an interacting particle system and observed striking memory effects in the dc magnetization and magnetic relaxation. 12 It has been suggested that the striking memory effects go beyond those previously observed in standard experiments and should be associated with a hierarchical model rather than a droplet model.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Different experimental approaches have been employed to observe the memory effect in spin-glass system and particle systems. [2][3][4][5][6][7][8][9][10] The most acceptable experimental approaches for observing the memory effect include low frequency ac susceptibility 2-8 ͑ = Ј+ Љ͒ and low field dc magnetization measurements. 5,6,9,10 The experimental details for each approach are briefly described as the following.…”
Section: Introductionmentioning
confidence: 99%
“…1(b)] indicating absence of spin glass order. In addition, another typical signature of spin glass relaxation, ''memory effect'' [23], was not observed in this material.…”
mentioning
confidence: 91%
“…Such relaxation can be even extended for a cooperative system like a spin glass with an additional input t w due to memory of historical events of the system [24]. One can readily test this fundamental signature by the principle of superposition, as follows [23,24]:…”
mentioning
confidence: 99%